2008
DOI: 10.1182/blood-2008-04-149393
|View full text |Cite
|
Sign up to set email alerts
|

Differential pattern of CD4+ and CD8+ T-cell immunity to MAGE-A1/A2/A3 in patients with monoclonal gammopathy of undetermined significance (MGUS) and multiple myeloma

Abstract: The factors that determine progression from monoclonal gammopathy of undetermined significance (MGUS) to multiple myeloma are unclear but may include the breakdown of immune surveillance. Cancer testis antigens (CTAgs) are expressed by the majority of myelomas and MGUS tumors and are a potential immune target. We have characterized CD4 ؉ and CD8 ؉ T-cell immune responses to MAGE-A1/ A2/A3 in these patients. CD4 ؉ T-cell immunity to MAGE proteins is stronger and more frequent in MGUS compared with myeloma with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…19 A similar pattern was observed in patient 125M with a diagnosis of MM who was initially studied more than 2 years after stem cell transplantation with a myeloablative conditioning regimen. The serum paraprotein level had risen at 124 weeks post-transplant and indicated the onset of disease relapse.…”
Section: Cancer-testis Antigen-specific Cd8mentioning
confidence: 55%
See 1 more Smart Citation
“…19 A similar pattern was observed in patient 125M with a diagnosis of MM who was initially studied more than 2 years after stem cell transplantation with a myeloablative conditioning regimen. The serum paraprotein level had risen at 124 weeks post-transplant and indicated the onset of disease relapse.…”
Section: Cancer-testis Antigen-specific Cd8mentioning
confidence: 55%
“…[10][11][12][13] CTAg-specific humoral and cellular immune responses have been reported in patients with a variety of solid tumors [14][15][16] and there is increasing interest in their potential role in hematopoietic malignancies. [17][18][19][20][21] CTAg may also represent an important target for the GvL effect of allogeneic transplantation and antibodies to CTAg proteins have been demonstrated in patients who have undergone stem cell transplantation for the treatment of myeloma. 21 A T-cell response to the CTAg protein NY-ESO was also observed in one patient in this cohort but this was coincident with disease relapse.…”
Section: Introductionmentioning
confidence: 99%
“…Myeloma is a malignancy which is thought to be controlled, at least © F e r r a t a S t o r t i F o u n d a t i o n to a certain extent, by the adaptive immune system, a view which is supported by the fact that the therapeutic effect of allogeneic stem cell transplantation is partly mediated by donor-derived T cells and that infusions of donor T cells are capable of inducing remission in relapsed MM patients. 42,43 We and others have recently shown that spontaneous antibody and T-cell immunity against MAGE-A3 and MAGE-C1/CT7 is present in patients with MM 10,[44][45][46] and that the presence of such immunity might be associated with an improved prognosis. 44 Our finding that immune responses against CT antigens are induced by allogeneic stem cell transplantation 10 suggests that these tumor antigens might indeed represent natural targets for donor-derived allo-immune or even spontaneous anti-myeloma immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 We and others have recently shown that spontaneous antibody and T-cell immunity against MAGE-A3 and MAGE-C1/CT7 is present in patients with MM 10,[44][45][46] and that the presence of such immunity might be associated with an improved prognosis. 44 Our finding that immune responses against CT antigens are induced by allogeneic stem cell transplantation 10 suggests that these tumor antigens might indeed represent natural targets for donor-derived allo-immune or even spontaneous anti-myeloma immune responses. Collectively, these findings indicate that T-cell-based immunotherapies might represent one therapeutic route for effective targeting of CT antigens.…”
Section: Discussionmentioning
confidence: 99%
“…46 Quintarelli et al 47,48 demonstrated PRAME-specific, cytotoxic lymphocyte cytotoxicity against chronic myelogenous leukemia cells. Goodyear et al 49 demonstrated the presence of CD8 þ , CTA-specific, cytotoxic lymphocytes in patients with MM, which, although the lymphocytes were unable to control tumor cell growth in vivo, lysed MM cells in vitro. Furthermore, patients with evidence of a CTA-specific immune response had a 53% reduction in mortality during a median follow-up of 4 years.…”
Section: Cancer/testis Antigens As Csc Immunotherapy Targetsmentioning
confidence: 99%